Pengembangan Modul Pembelajaran Mata Pelajaran Pengecatan Bodi Pada SMK Program Keahlian Teknik Bodi Otomotif - Ryandika, Aldian; Rabiman, Rabiman; Purnomo, Sigit (Jurnal Pendidikan Vokasi Otomotif, 2024)
This research is a development research (research and development) with the development of learning media in the form of Automotive Body Engineering modules in Class XI Body Painting Subjects at SMK Kristen 5 Klaten using the Four-D method by Thiagarajan and Semmel which has been modified. The stages used in the module development process are the defining stage (define), the design stage (design), the development stage (develop) and the dissemination stage (disseminate). Collecting feasibility data using questionnaires and observations. This study involved material experts, media experts, subject teachers and students to obtain module feasibility assessments and responses. The data analysis technique used was quantitative descriptive analysis.The results showed that: 1) produce an Automotive Body Engineering learning module; 2) the Automotive Body Engineering learning module at SMK Kristen 5 Klaten is feasible to use based on the results of material expert validation with a percentage of 76.08% and the results of validation by media experts with a percentage of 73.80% with a decent category; The results of the assessment of the feasibility level of the Automotive Body Engineering learning module at SMK Kristen 5 Klaten by the subject teacher with a percentage of 88.23% with a decent category; 4) The results of the assessment response from class XI students were 94.14% with a very feasible category.